Genome-wide association analysis uncovers rice blast resistance alleles of Ptr and Pia - Greenwood, Julian R.; Lacorte-Apostol, Vanica; Kroj, Thomas; Padilla, Jonas; Telebanco-Yanoria, Mary Jeanie; Glaus, Anna N.; Roulin, Anne; Padilla, André; Zhou, Bo; Keller, Beat; Krattinger, Simon G. (Springer, 2024)
A critical step to maximize the usefulness of genome-wide association studies (GWAS) in plant breeding is the identification and validation of candidate genes underlying genetic associations. This is of particular importance in disease resistance breeding where allelic variants of resistance genes often confer resistance to distinct populations, or races, of a pathogen. Here, we perform a genome-wide association analysis of rice blast resistance in 500 genetically diverse rice accessions. To facilitate candidate gene identification, we produce de-novo genome assemblies of ten rice accessions with various rice blast resistance associations. These genome assemblies facilitate the identification and functional validation of novel alleles of the rice blast resistance genes Ptr and Pia. We uncover an allelic series for the unusual Ptr rice blast resistance gene, and additional alleles of the Pia resistance genes RGA4 and RGA5. By linking these associations to three thousand rice genomes we provide a useful tool to inform future rice blast breeding efforts. Our work shows that GWAS in combination with whole-genome sequencing is a powerful tool for gene cloning and to facilitate selection of specific resistance alleles for plant breeding.